Fast analytical design of maximally flat notch fir filters - Zahradnik, Pavel; Vlcek, Miroslav (Communications - Scientific letters of the University of Zilina, 2004)
A novel fast analytical design procedure for the maximally flat notch FIR filters is introduced. The closed form solution provides recursive evaluation of the impulse response coefficients of the filter. The discrete nature of the notch frequency is emphasized. One design example is included to demonstrate the efficiency of the presented approach.